Cross-Talk between Tight and Anchoring Junctions—Lesson from the Testis - Yan, Helen H.N. (2008)
Spermatogenesis takes place in the seminiferous tubules in adult testes such as rats, in which developing germ cells must traverse the seminiferous epithelium while spermatogonia (2n, diploid) undergo mitotic and meiotic divisions, and differentiate into elongated spermatids (1n, haploid). It is conceivable that this event involves extensive junction restructuring particularly at the blood-testis barrier (BTB, a structure that segregates the seminiferous epithelium into the basal and the adluminal compartments) that occurs at stages VII–VIII of the seminiferous epithelial cycle. As such, cross-talk between tight (TJ) and anchoring junctions [e.g., basal ectoplasmic specialization (basal ES), adherens junction (AJ), desmosome-like junction (DJ)] at the BTB must occur to coordinate the transient opening of the BTB to facilitate preleptotene spermatocyte migration. Interestingly, while there are extensively restructuring at the BTB during the epithelial cycle, the immunological barrier function of the BTB must be maintained without disruption even transiently. Recent studies using the androgen suppression and Adjudin models have shown that anchoring junction restructuring that leads to germ cell loss from the seminiferous epithelium also promotes the production of AJ (e.g., basal ES) proteins (such as N-cadherins, catenins) at the BTB site. We postulate the testis is using a similar mechanism during spermatogenesis at stage VIII of the epithelial cycle that these induced basal ES proteins, likely form a “patch” surrounding the BTB, transiently maintain the BTB integrity while TJ is “opened”, such as induced by TGF-b3 or TNFa, to facilitate preleptotene spermatocyte migration. However, in other stages of the epithelial cycle other than VII and VIII when the BTB remains “closed” (for ~10 days), anchoring junctions (e.g., AJ, DJ, and apical ES) restructuring continues to facilitate germ cell movement. Interestingly, the mechanism(s) that governs this communication between TJ and anchoring junction (e.g., basal ES and AJ) in the testis has remained obscure until recently. Herein, we provide a critical review based on the recently available data regarding the cross-talk between TJ and anchoring junction to allow simultaneous maintenance of the BTB and germ cell movement across the seminiferous epithelium.